(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article deals with the problem of the "lost generation" in the international and Ukrainian artists’ works devoted to the events of the First World War, The Civil War and post-war reality. In a comparative aspect the attention drawn to the similarity of heroes’ worldviews created by Ukrainian and German writers, characters’ feeling of the absurdity of the existence and attempts to overcome the existential vacuum.